The Optimization of Addition of Bromelain Enzyme Catalyst on the Fermentation of Coconut Milk to VCO (Virgin Coconut Oil) Using Tempeh Yeast - Rahmalia, Itta; Kusumayanti, Heny (Vocational College of Universitas Diponegoro, 2021)
Coconut (Cocos nucifera) is one of the most abundant tropical plants in Indonesia. It is proven that in 2020 the total area of coconut plantations in Indonesia reached 3,377,376 hectares. Virgin Coconut Oil (VCO) is one of the diversified coconut products with high commercial value. In this study, the production of Virgin Coconut Oil (VCO) was carried out by fermenting tempeh yeast and with the help of the bromelain enzyme as a catalyst. This is because the bromelain enzyme is a type of protease enzyme that acts as a protein breaker in the oil contained in the coconut milk emulsion. Research has shown that the concentration of the bromelain enzyme affects the yield of VCO. Virgin Coconut Oil (VCO) with the addition of 6 grams of bromelain enzyme, 30 hours of fermentation time, and the use of 2 grams of tempeh yeast resulted in the highest yield value of 9.2% and free fatty acids (FFA) of 0.21%. This is because the higher the bromelain enzyme concentration, the more it will bind to protein as a substrate. In addition, the longer the fermentation, the more hydrolysis that occurs in the oil, so that the fermentation time also affects the concentration of free fatty acids of VCO. Analysis of fatty acid content was carried out using the GCMS method and showed that the highest fatty acid content was lauric acid at 54.27%. While the physical characterization of the resulting VCO is in accordance with SNI 7381:2018, which has a distinctive smell of coconut aroma, a distinctive taste of coconut oil, and is colorless.